The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1136/gutjnl-2014-309026
|View full text |Cite
|
Sign up to set email alerts
|

Activating ERBB2/HER2 mutations indicate susceptibility to pan-HER inhibitors in Lynch and Lynch-like colorectal cancer

Abstract: We developed a high-throughput deep sequencing approach for concomitant MSI and mutational analyses in FFPE specimens. We provided novel insights into clinically relevant alterations in MSI CRC and a rationale for targeting ERBB2/HER2 mutations in Lynch and Lynch-like CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 45 publications
4
55
1
1
Order By: Relevance
“…While this paper was under review, Kloth and colleagues published that 15% of Lynch syndrome or Lynch-like CRC have HER2 mutations and they showed that the HER2 mutant CRC cell lines, CW-2 and CCK-81, are sensitive to treatment with neratinib and afatinib (31). Our PDX results suggest that dual HER2 targeted therapy may be needed to achieve optimum anti-tumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…While this paper was under review, Kloth and colleagues published that 15% of Lynch syndrome or Lynch-like CRC have HER2 mutations and they showed that the HER2 mutant CRC cell lines, CW-2 and CCK-81, are sensitive to treatment with neratinib and afatinib (31). Our PDX results suggest that dual HER2 targeted therapy may be needed to achieve optimum anti-tumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of microsatellite status was performed with the previously described methods. 46 For examination of somatic APC mutations, targeted sequencing with high coverage (read depths > 1000) was performed using the FAP MASTR Kit (Multiplicom) on a MiSeq platform (Illumina) in one person (individual 1661.1). The results were analyzed with the SeqPilot software (JSI Medical Systems).…”
Section: Methodsmentioning
confidence: 99%
“…46 This involved use of the National Cancer Institute (NCI) reference marker panel for the evaluation of microsatellite instability (MSI) in colorectal cancer. This panel consists of two mononucleotide (BAT25, BAT26), and three dinucleotide (D2S123, D5S346 and D17S250) repeats.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, however, ERBB2 mutations at such hotspot loci were reported to be recurrent in MSI CRC. Kloth et al (8) reported that 15% of BRAF wild-type MSI CRC harbor ERBB2 mutations with these tumors harboring highly recurrent L755S and V842I substitutions, as well as new variants L726F, A848T and G865R. In that study, MSI CRC cell lines harboring such ERBB2 mutations were highly sensitive to irreversible EGFR/ERBB2 small molecule tyrosine kinase inhibitors, highlighting their potential role in the treatment of ERBB2 mutated CRC regardless of mismatch repair status.…”
mentioning
confidence: 88%